2021
DOI: 10.1021/acs.jpca.1c06434
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Morphology Controls Reactivity of OH Radicals at the Air–Ice Interface

Abstract: At the air−ice interface, some aromatic compounds such as benzene and anthracene are surprisingly unreactive toward OH. This may be a consequence of the poor solvation of these compounds at the interface, resulting in clustering there. We test this hypothesis by comparing the reaction of OH with pyrene, a 4ring polyaromatic hydrocarbon (PAH), to reactions of OH with the more water-soluble compounds coumarin and 7-hydroxycoumarin (7OHC). We observe that OH reacts readily with coumarin and 7OHC at both liquid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
(92 reference statements)
1
5
0
Order By: Relevance
“…The preference of H 2 O 2 for grain boundaries in environmental snow and ice might result in significant variations in the local concentration of H 2 O 2 . This is relevant as such non-uniform chemical morphologies and highly concentrated patches of reactants at grain boundaries and elsewhere in the ice have recently been shown to impact chemical reactivity in frozen systems strongly. ,, Grain boundaries in natural snowpacks occur at the contact face of individual snow grains . As grain size, shape, and arrangement change with time in snowpacks (metamorphism), detailed studies observing the impact of grain boundaries at different stages of metamorphism are timely to elucidate the mechanism and the environmental impact more extensively.…”
Section: Resultsmentioning
confidence: 99%
“…The preference of H 2 O 2 for grain boundaries in environmental snow and ice might result in significant variations in the local concentration of H 2 O 2 . This is relevant as such non-uniform chemical morphologies and highly concentrated patches of reactants at grain boundaries and elsewhere in the ice have recently been shown to impact chemical reactivity in frozen systems strongly. ,, Grain boundaries in natural snowpacks occur at the contact face of individual snow grains . As grain size, shape, and arrangement change with time in snowpacks (metamorphism), detailed studies observing the impact of grain boundaries at different stages of metamorphism are timely to elucidate the mechanism and the environmental impact more extensively.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence experiments were carried out using a setup based on those we have used in the past, and described fully in McLay et al The unfocused output of a wavelength-tunable pulsed Nd:YAG laser-pumped optical parametric oscillator (OPO) system operating at a pulse frequency of 20 Hz was directed toward either a circular sample dish, 6 cm in diameter and about 1 cm deep, or a 1 cm path-length cuvette. Typical pulse energies at the laser head were between ∼0.5 and ∼1.2 mJ per 3 ns pulse.…”
Section: Methodsmentioning
confidence: 97%
“…A complete spectrum was not measured, either in the bulk or at the surface. Previous work 31,33,35 has shown that the bulk aqueous and aqueous surface fluorescence spectra are essentially identical for clean water surfaces. The luminol fluorescence intensity at 420 nm was monitored following excitation at 350 nm in the bulk and at the water surface as a function of the concentration of added salt.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…15 The GALIF technique used in these experiments was developed and has been used over the past two decades to investigate surface partitioning, pH and reaction kinetics at a variety of environmentally relevant surfaces. [15][16][17][18][19][20] For example, Mmereki et al 16 measured the surface uptake coefficients of anthracene and pyrene from the gas phase to freshwater surfaces and to octanol-and hexanoic acid-coated surfaces. A 2-3 times enhancement in the surface uptake coefficient was seen when octanol was present at the surface, as compared to when the surface was freshwater.…”
Section: Introductionmentioning
confidence: 99%